An Ecotheological Study of Patchouli Cultivation Practices among the Congregation of GMIM Kanaan Karowa, Tompasobaru I Region - Poluan, Sindy Claudia; Poluan, Agnes Relly; Mawikere, Marde Christian Stenly (Peneliti.net, 2025)
This study examines the implementation of ecotheological values in the patchouli (Pogostemon cablin) farming practices of the GMIM Kanaan Karowa congregation in the Tompasobaru I region. Employing a descriptive qualitative approach, data were gathered through in-depth interviews, field observations, and church document analysis. The findings reveal a significant gap between the congregation’s strong theological awareness regarding the responsibility to care for creation and the reality of environmentally unfriendly agricultural practices. The community remains dependent on chemical fertilisers, pesticides, and wood-fuelled distillation methods that pose ecological risks. The church’s role is still confined to doctrinal teaching, lacking structured ecological action. Therefore, the church must take a leading role in integrating faith with ecological engagement to promote sustainable agriculture in harmony with Christian belief and the integrity of creation.